Subjective Outcome Evaluation Based on Secondary Data Analyses: The Project P.A.T.H.S. in Hong Kong - Daniel T.L. Shek; Rachel C.F. Sun (The Scientific World Journal)
The intent of this study was to evaluate the program effectiveness of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) (Secondary 1 Curriculum) by analyzing 207 school-based program reports, in which program implementers were invited to write down five conclusions based on an integration of the subjective outcome evaluation data collected from the program participants and program implementers. Secondary data analyses were conducted and 1,855 meaningful units were extracted from 1,035 “aggregated” conclusions. Among them, about 27 and 18% were related to perceptions of the program and implementers, respectively, and most of them were positive in nature. About one-third was related to perceived effectiveness of the program, and most of them referred to enhancement of students' development in societal, familial, interpersonal, and personal aspects. However, difficulties encountered during program implementation (3.34%) and recommendations for improvement (18.11%) were also reported. The present study replicated the findings reported in previous studies and suggests that the Tier 1 Program of the Project P.A.T.H.S. is beneficial to the development of the program participants.